Three-dimensional FE/NCV Simulation of Pultrusion Process with Temperature-dependent Material Properties including Resin Shrinkage - Joshi, Sunil Chandrakant (2015)
This paper discusses the development and application of the finite-element/nodal-control-volume (FE/NCV) approach for three-dimensional pultrusion analysis. A numerical procedure is designed which uses a combination of the field analysis module of a general-purpose finite-element package and a few user-written computer codes. Numerical schemes employed for calculating the effects of convective heat-transfer on temperature and degree of cure, for modelling resin cure kinetics and the effects of temperature-dependent material properties, and for determining the dimensional changes due to chemical shrinkage and thermal expansion of resin are discussed in detail. Case studies are presented demonstrating the simulation of the pultrusion process for different components including irregular and hollow sections.